Fabrication of crystalline porphyrinic polyoxometalate cluster with high thermal stability and exploration of its photocatalytic activity. (10th January 2017) - Zhang, Junyong; Gong, Chunhua; Zeng, Xianghua; Shu, Jiahui; Xiao, Pingxiu; Xie, Jingli
Graphical abstract: Crystalline porphyrinic polyoxometalate hybrid H8 [C40 H26 N8 ]3 [SiW12 O40 ]2 ·(H2 O)5 ·(CH3 CN)2 (1 ) shows high structural robustness confirmed by crystallographic determination and thermal analysis. Photocatalytic activities are observed in the reduction process of metal compositions to achieve Au nanosheets/Ag nanoparticles as well as the degrading of Parafuchsin Hydrochloride dye. Abstract: Crystalline porphyrinic polyoxometalate hybrid H8 [C40 H26 N8 ]3 [SiW12 O40 ]2 ·(H2 O)5 ·(CH3 CN)2 (1 ) shows high structural robustness confirmed by crystallographic determination and thermal analysis. Photocatalytic activities are observed in the reduction process of metal compositions to achieve Au nanosheets/Ag nanoparticles as well as the degrading of Parafuchsin Hydrochloride dye.